Neanotis prabhuii, a new species of Rubiaceae from Western Ghats, India - Sunil, Chandrasseril Narayanan; Salim, Pichan Mohammed; Narayanan, Matalai Kokkarammath Ratheesh; Nithya, Vadassery Madhanan; Sanilkumar, Malayil Gopalan; Anilkumar, Nadesapanicker (Phytotaxa, 2021)
N/A